2000
DOI: 10.1002/(sici)1521-3765(20000117)6:2<321::aid-chem321>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Formal Fusion of a Pyrrole Ring onto 2-Pyridyl and 2-Pyrimidyl Cations: One-Step Gas-Phase Synthesis of Indolizine and Its Derivatives

Abstract: Two ortho-hetarynium ions, the 2-pyridyl and 2-pyrimidyl cations, react promptly with 1,3-dienes in the gas phase by annulation, formally by fusion, onto the ions of a pyrrole ring. This novel reaction proceeds through an initial polar [4 + 2+] cycloaddition across the C[triple bond]N+ bond, followed by fast ring opening, a [1,4-H] shift, and finally a recyclization that results in a contraction of a six- to a five-membered ring and dissociation by the loss of a methyl radical. For the 2-pyridyl cation, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…39 The loss of a hydrogen atom leads to the formation of a cationic hetero-aryne, which are known to be very reactive even towards closed–shell molecules. 40 To investigate this further we have performed experiments, where we admitted a mix of 5% acetylene in helium to the ion trap. The resulting mass spectrum is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…39 The loss of a hydrogen atom leads to the formation of a cationic hetero-aryne, which are known to be very reactive even towards closed–shell molecules. 40 To investigate this further we have performed experiments, where we admitted a mix of 5% acetylene in helium to the ion trap. The resulting mass spectrum is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this study did not explore the mechanisms of reactions of 6 . Another charged pyridyne, the 2-pyridyl cation 4 , has been the focus of several gas-phase and solution experimental and theoretical studies. Mass spectrometric studies, supported by density functional theory (DFT) calculations, indicated greater thermodynamic stability (on the basis of calculated relative enthalpies of formation) for the 2-pyridyl cation 4 than for the isomeric 3- and 4-pyridyl cations. , Further, polar cycloaddition reactions were reported for 4 in solution. , This reactivity resembles that of neutral arynes and heteroarynes in solution. , Additionally, a gas-phase reactivity study on the 2-pyridyl cation indicated that this cation can undergo formal anion (hydride, iodide) or group ( e.g ., methylmercaptan, allene) abstraction reactions when allowed to react with cyclohexane, allyl iodide, and dimethyl disulfide . However, differences in the reactivities of the two neutral ortho -pyridynes and the three charged ortho -pyridynes have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed new reactions and shed light to intrinsic reactivity and reaction mechanisms, and important analytical and synthetic uses for these ion/molecule reactions have been found. The intrinsic (free of solvent and counter ion effects) concerted or stepwise polar cycloaddition reactivity of many classes of gaseous ions have been investigated such as for ionized alkenes, fullerenes, ylides, nitrilium and immonium ions, hetarynium ions, cyclic N‐acyl and N, N‐diacyliminium ions, the nitronium ion, protonated and methylated azabutadienes, phosphenium ions, phosphirenylium ion, ionized α‐oxoketene and the phenyl sulfinyl cation . Perhaps, the most systematically studied class of gas‐phase polar cycloadditions has been the [4 + 2 + ] cycloadditions involving acylium ions (R‐C + = O) and dienes or heterodynes .…”
Section: Introductionmentioning
confidence: 99%